Professional and technological education: historical path and challenges in teacher education (Research, Society and Development, 2020)
This article aims to present the trajectory of Professional and Technological Education in Brazil, taking into account the changes that ETP presents in its legal frameworks and teacher training, including when taking the curriculum as a reference, discussing teaching in the world Professional and Technological Education, without disregarding elements such as omnilaterality and integration of high school. The research is justified in rescuing the historical context of EFA in Brazil and understanding how its chronology contributes to the qualification of its teachers. In this sense, it was decided to use a methodology with a quantitative approach and literature review, carried out on materials published in written and electronic media, such as E-books, books and scientific articles. Thus, it was possible to see that the changes that occurred during the historic journey of EPT and the struggle of teachers.